UPDATE OF WIND CARTOGRAPHY IN CENTRAL AND SOUTHERN NEUQUÉN - Samuel D. Troncoso Schenker; Lidia Ferreyra; Claudia Palese (Boletín Geográfico)
In recent years the use of the wind resource was increased not only for diversifying the electricity generation matrix of the countries but also to supply energy for small settlements that are isolated from electricity grids. The objective of this work was to update the Wind Resource Map of the Province of Neuquén, in order to have updated wind cartography that provides the basis for feasibility studies of wind power generation projects. New wind data of excellent quality existing in the area was used. In this study, a diagnostic mass consistent model that allows managing databases was used. The relief and surface roughness were elaborated with remote sensors data. The parameters of the local atmospheric boundary layer were obtained from an atmospheric model outputs. The wind map at 50 meters height and the directional wind characteristics in points of mesh of the centre and southern of the Province of Neuquén was obtained. The quality of fit between the model results and the measurements was evaluated. Wind cartography of adequate quality (ε r = 0.069 and r > 0.93) was achieved, especially in the west sector (ε r < 0.04 and r > 0.98), which are the predominant and most intense wind directions in the region. Excellent wind quality location, near good routes and power lines, as, among others, the Barda Negra Plateau and the Vaca Muerta Plateau, in which the annual average wind speed at 50 meters height exceeded 9.0 m/s and at west directions 14.0 m/s. This fact indicates the possibility of installing wind farms.